Ethics of Responsibility and Rationality of Praxis. Schopenhauer in Perspective: A look at corporate social responsibility - Prats-Palma, Belisario; Villalobos-Antúnez, José Vicente; Severino-González, Pedro; Sepúlveda De la Jara, Flavia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The concept of ethics of responsibility is approached from a double perspective: from the rationality of the praxis that unfolds the subject seen as an individual, but also from the idea of solidarity necessary to form a philosophical fabric that addresses business ethics in a comprehensive sense. Under the concept of philosophy of praxis, it is interpreted the concept of moral conscience and then addresses the concept of social responsibility as necessary praxis of action. It is concluded from Schopenhauer’s ethics that the moral individual must be seen in his social dimension to overcome the difficulties of egoism.